Effects of Mental Fatigue on Football Referee Decision Making (Universitas Pendidikan Indonesia, 2025)
Referee is an important element in a football match. Just like an athlete, the mental aspect of a referee also greatly affects the performance of a football referee. This study aimed to determine the effect of mental fatigue on football referee decision making. The method used in this study was an experimental method with a pre-post-test design. Participants of this study consisted of 28 football referees selected using a purposive sampling technique. Participants consisted of male referees with amateur and professional background levels and having more than three years of experience. In this study, the FIFA Video test 2024 was used as a decision-making instrument. Based on the results of data processing and analysis using the paired sample T-Test, a significance value of 0.000 was obtained, indicating that there was a significant effect of mental fatigue on football referee decision making. This indicates that a referee ability to manage psychological aspects can help them overcome mental fatigue which could affect referees in making the right decisions in football matches.